X-ray Thomson scattering on shocked graphite - Kraus, D; Otten, A; Frank, A; Bagnoud, V; Blazevic, A; Gericke, DO; Gregori, G; Ortner, A; Schaumann, G; Schumacher, D; Vorberger, J; Wagner, F; et al. (2012)
We present measurements of the changes in the microscopic structure of graphite in a laser-driven shock experiment with X-ray scattering. Laser radiation with intensities of ∼2 × 10 13 W/cm 2 compressed the carbon samples by a factor of two reaching pressures of ∼90 GPa. Due to the change of the crystalline structure the scattered signals of the probe radiation were modified significantly in intensity and spectral composition compared to the scattering on cold samples. It is shown that the elastic scattering on tightly bound electrons increases strongly due to the phase transition whereas the inelastic scattering on weakly bound electrons remains nearly unchanged for the chosen geometry. © 2011 Elsevier B.V.